Towards inclusive teaching: Finnish teachers' justifications for co-teaching - Marjut Kokko; Päivi Pihlaja; Marjatta Takala (University of Aberdeen, School of Education, 2022)
The Finnish school system is associated with the provision of inclusive values, such as equality and equal opportunity for all. In recent years, the pupils attending regular schools have become more heterogeneous and the number of pupils in need of support has grown. This study examines teachers' perceptions of when the implementation of co-teaching is justified and when it is not justified. Co-teaching, which means teaching together with another teacher, is one way to organise pedagogical support in the general education group. Although several studies have reported the benefits and challenges of co-teaching, researchers have not reached an agreement on the situations where teachers see co-teaching as justified. Most Finnish teachers have a positive attitude towards co-teaching, yet its degree of implementation is low. The data have been collected from primary education teachers (N = 432) in Finland and analysed in a data-driven manner adopting a grounded theory approach. The results of the research show that the teachers' arguments for implementing co-teaching are contradictory. Moreover, their attitudes towards inclusion are reflected in their perceptions of co-teaching. The justifications for co-teaching are the benefits gained through collaboration and the support for education. Most differences in opinions occur when pupils in need of various kinds of special support are integrated into the general education group.